2017
DOI: 10.1016/s2213-8587(16)30321-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative prognostic performance of definitions of prediabetes: a prospective cohort analysis of the Atherosclerosis Risk in Communities (ARIC) study

Abstract: Background There is a lack of consensus across international organizations regarding definitions of prediabetes. Associations with complications can inform the comparative value of different prediabetes definitions. Methods We conducted a prospective cohort study of 10,844 Atherosclerosis Risk in Communities (ARIC) study participants without diagnosed diabetes who attended visit 2 (1990–92) and 7,194 who attended visit 4 (1996–98). Fasting glucose and HbA1c were measured at visit 2 and fasting glucose and 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(142 citation statements)
references
References 22 publications
8
125
1
6
Order By: Relevance
“…The definition of prediabetes is controversial given 5 different fasting glucose and HbA 1c criteria with differing sensitivities and specificities (Table ) resulting in differing prevalence and clinical outcomes . Warren et al recently compared these tests and threshold levels for identifying prediabetes extending previous observations demonstrating different and overlapping prevalence of prediabetes according to the definition used …”
Section: Introductionmentioning
confidence: 99%
“…The definition of prediabetes is controversial given 5 different fasting glucose and HbA 1c criteria with differing sensitivities and specificities (Table ) resulting in differing prevalence and clinical outcomes . Warren et al recently compared these tests and threshold levels for identifying prediabetes extending previous observations demonstrating different and overlapping prevalence of prediabetes according to the definition used …”
Section: Introductionmentioning
confidence: 99%
“…The Sheffield group models (Gillett 2015, Breeze 2016) and the CDC/University of Michigan group models (Hoerger 2007, Herman 2005) reported that they explicitly based their diabetes models on previous T2D decision model(s). Three studies (Gillett 2015, Breeze 2016 and Herman 2005) developed new T2D model structures but reported these to be based on previous T2D models, such as Eastman 1997 . The remaining studies reported an apparently new model structure, with the aim of addressing their particular research question.…”
Section: Resultsmentioning
confidence: 99%
“…The variation seemed to be largely a function of the clinical studies used to inform the model and their inclusion criteria, as well as changes in the classification and diagnosis of (pre)diabetes over time. This is relevant, as disease progression will differ according to the definition of prediabetes . For example, IFG and IGT are considered distinct pathophysiological mechanisms and may lead to differing risks of developing diabetes or complications .…”
Section: Discussionmentioning
confidence: 99%
“…GPC-2015-51, recognizes the terms increased risk of diabetes or prediabetes, recommending that people with a score equal to or greater than 12 on the Findrisk scale but do not meet diagnostic criteria for DM2, should establish the presence of increased risk categories of diabetes for inclusion in DM2 prevention programs Table 3 1 . [56][57][58][59][60][61] . A study in Colombia showed that hyperglycaemia was associated with a greater number of adverse outcomes in 439 individuals who survived a first acute myocardial infarction (AMI).…”
Section: What Do the Guidelines Say About Prediabetes?mentioning
confidence: 99%